Edukasi Pengembangan SDM dan Kualitas Kerja pada Remaja Mesjid Rabithah Medan - Juniarti Juniarti; Zetary, Luriandra Nadhifa (BADAN PENERBIT STIEPARI PRESS, 2022)
The purpose of this community service is to improve human resource development education and work quality in Rabithah mosque youth. The specific target in this community service is for Rabithah mosque teenagers to know what Human Resources development and work quality are. The materials presented in this community service are: what is human resources and work quality. The connection will affect the increase in understanding of the development of human resources so that Rabithah mosque teenagers get solutions to human resource development and work quality. From this community service, it shows the results that Rabithah mosque teenagers already know and understand the importance of insight into Human Resources development and work quality so that they can improve work performance.